Analysing the influence of customer satisfaction and brand trust on improving customer retention and loyalty - Maheswari, Made Triana; Yudistira , Cokorda Gede Putra; Rumini , Ni Luh Putu Inten; Kasiani, Kasiani; Kencanawati, Anak Agung Ayu Mirah; Marheni, Lily; Sarjana, I Made (Yayasan Mitra Persada Nusantara, 2025)
The purpose of this study is to determine the influence of customer satisfaction and trust in brand partially or simultaneously on customer retention of Hyatt Regency Bali customers. This research is of a quantitative type. The analysis technique used is multiple linear regression analysis. Sampling was done with purposive sampling with a sample of 97 respondents. The data collection instrument uses a questionnaire with a closed statement. Data analysis used parametric inferential statistical analysis. Simultaneous testing showed a significant influence of the variables of customer satisfaction and trust in brand on customer retention with a Sig. value of 0.000<0.1 and a Calculation value of 106.219>Table 2.36. Partial testing showed a significant influence of customer satisfaction variables on customer retention with a Sig. value of 0.000<0.1 and a calculation of 3.853>table 1.66123. Partial testing also showed a significant influence of the trust in brand variable on customer retention with a Sig. value of 0.000<0.1 and a calculation of 7.303> t-table 1.66123. This result is strengthened by the acquisition of a determination coefficient value of 68.7% of customer retention, which can be explained by variations in customer satisfaction and trust in brand. The remaining 31.3% were explained by other causes that were not mentioned in this study. It can be concluded that Hyatt Regency Bali increases customer retention by increasing customer satisfaction and trust in the brand so that it can be known the strategies that must be done to increase the customer retention rate.